DENGUE IN PREGNANT WOMEN: A POTENTIAL THREAT TO MATERNAL-FETAL OUTCOMES? - Romão , Marcela Pereira; Rubira , Lara Zaccarelli; Chehter , Ethel Zimberg (Seven Editora, 2024)
INTRODUCTION: Dengue is an acute febrile disease caused by the DENV virus and transmitted mainly by the Aedes mosquito. It is an endemic disease mainly in countries in Asia and America. The clinical course is usually divided into three phases: febrile, critical and recovery, with fever being the initial symptom, sometimes accompanied by anorexia, vomiting, diarrhea and maculopapular rash. The critical phase is characterized by increased capillary permeability, which results in hemorrhage, shock and organ dysfunction due to fluid accumulation, gradually reabsorbed in the recovery phase. The diagnosis of dengue is made based on the detection of the NS1 antigen; the genome, by RT-PCR; or IgM or IgG antibodies. Treatment is only symptomatic. During pregnancy, studies suggest that there is an increase in adverse maternal-fetal outcomes due to DENV infection, in addition to the challenging diagnosis, due to the physiological adaptations of pregnancy. In this context, this systematic review aims to analyze how dengue behaves in pregnant women and the outcome of the infection. METHOD: searches were performed in PubMed, using the keywords “dengue pregnancy”, in LILACS, using “dengue pregnancy” and “dengue embarazo”, and in Scielo, using “dengue pregnancy”. A total of 188, 18, 21 and 1 results were obtained, respectively, and after exclusion by title and abstract, and by full text, 32 articles were included. RESULT: of the maternal outcomes, severe thrombocytopenia and death were the most cited in the articles, followed by postpartum hemorrhage, more severe forms of the disease, need for cesarean section and preeclampsia. The most prevalent fetal repercussion was prematurity, in addition to stillbirths, neonatal deaths, low birth weight and oligohydramnios. DISCUSSION: The articles analyzed suggest that dengue during pregnancy increases the risk of severe forms of the disease, postpartum hemorrhage, maternal death, miscarriage, stillbirths, fetal growth restriction, prematurity, and oligohydramnios, especially in cases of infections acquired in the third trimester of pregnancy. Vertical transmission also increases at the end of pregnancy. CONCLUSION: This review highlights that dengue is especially relevant during pregnancy, with a significant negative impact on maternal and fetal outcomes. However, further studies are still needed for greater depth, since there is no consensus. DOI:https://doi.org/10.56238/sevened2024.037-033